Archetypes, Angels and Gaia - Osborne, Lawrence (Journal for the study of religion, nature and culture, 2001)
Since its formulation in the 1960s by James Lovelock, the Gaia hypothesis has, as Lawrence Joseph’s comprehensive summary indicates, fulfilled a wide variety of needs among environmentalists, feminists and New Agers. This very variety is a source of confusion and even conflict, with New Agers and self-proclaimed Gaian philosophers criticizing Lovelock for the conservatism of his interpretation.